(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The current research aims to explain the concept of the three-line model issued by the American Institute of Internal Auditors (IIA) as a new concept related to controlling accounting practices, especially its new role in evaluating and improving risk and opportunity management systems, and its role in providing its services to all parties concerned with the unit in a way that contributes to achieving value. Added to the economic unit, in addition to the involvement of all administrative and operational entities working in the economic unit, as it describes the financial and non-financial influences on each other in preparing integrated reports according to what was stated by the Integrated Reporting Council (IIRC), as the researchers adopted the statistical method to prove the hypothesis by building A questionnaire included three main axes: explaining the concept and roles of the three-line model issued by the IIA, the second axis explaining the concept of integrated reports, and the third and final axis was devoted to enhancing the value of the economic unit through the role of the three-line model in improving integrated reports, as (65) paper questionnaires were distributed. On the research sample, (58) questionnaires were retrieved, and (52) questionnaires were valid for analysis. The questionnaire was also sent electronically to a group of employees. (26) questionnaires were answered, making the total number (78), as the descriptive analytical approach was adopted in analyzing the results of the questionnaire and linking them to the results, and testing the hypothesis through Using the Statistical Package for the Social Sciences (SPSS), and one of the most important results reached is that the three lines model issued by the IIA has a positive impact on the performance of economic units, and is also considered one of the important and necessary mechanisms in enhancing the reliability of integrated reports because they contain information of great importance to decision makers to enhance From the value of economic units, the research also recommended the necessity of applying the three-line model issued by the IIA in a mandatory manner in economic units to manage risks and activate the principles of governance, internal auditing and internal control, to enhance transparency and reliability in the data disclosed within the integrated reports of the economic unit.